2020
DOI: 10.1002/pmic.201900375
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Sperm Oxidation: Breaking Down the Origins of Oxidative Activity

Abstract: Oxidative stress has been long considered an important cause of male infertility, and sperm-derived reactive oxygen species (ROS) have been considered one of the major sources. In article number 1900205, Issue 2, Netherton et al. have improved upon current technologies for detection of true ROS-derived oxidative events from those originated by mitochondrial compounds. Moreover, the authors have isolated proteins that bear lipid aldehyde adducts, in order to verify their origin. In their paper, Netherton et al.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In contrast, some studies have demonstrated no correlation between ROS and sperm motility (Pasqualotto, Sharma, Nelson, Thomas, & Agarwal, 2000). In fact, ROS may result in decreased axonemal protein phosphorylation and reduced membrane fluidity (Bertolla, 2020). Certain ROS, like H 2 O 2 , can diffuse across cellular membranes and disrupt enzyme activity, such as with G6PD (Zandalinas & Mittler, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, some studies have demonstrated no correlation between ROS and sperm motility (Pasqualotto, Sharma, Nelson, Thomas, & Agarwal, 2000). In fact, ROS may result in decreased axonemal protein phosphorylation and reduced membrane fluidity (Bertolla, 2020). Certain ROS, like H 2 O 2 , can diffuse across cellular membranes and disrupt enzyme activity, such as with G6PD (Zandalinas & Mittler, 2018).…”
Section: Discussionmentioning
confidence: 99%